ХУДОЖЕСТВЕННЫЙ ПЕРЕВОД КАК ОДНО ИЗ КЛЮЧЕВЫХ НАПРАВЛЕНИЙ СРАВНИТЕЛЬНОГО ЛИТЕРАТУРОВЕДЕНИЯ - Шукурова Ф.Х (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
In this article, literary translation is considered as one of the ways of development of literature. Literary translation brings peoples together, drawing a connecting thread between them. Literary translation is one of the key areas of comparative literature.